Threatening drug‐drug interaction in a kidney transplant patient with coronavirus disease 2019 (COVID‐19). Issue 4 (14th July 2020) - Bartiromo, Marilù; Borchi, Beatrice; Botta, Annarita; Bagalà, Alfredo; Lugli, Gianmarco; Tilli, Marta; Cavallo, Annalisa; Xhaferi, Brunilda; Cutruzzulà, Roberta; Vaglio, Augusto; Bresci, Silvia; Larti, Aida; et al.
Abstract: During the novel coronavirus pandemic, organ transplant recipients represent a frail susceptible category due to long‐term immunosuppressive therapy. For this reason, clinical manifestations may differ from general population and different treatment approaches may be needed. We present the case of a 36‐year‐old kidney‐transplanted woman affected by Senior‐Loken syndrome diagnosed with COVID‐19 pneumonia after a contact with her positive mother. Initial symptoms were fatigue, dry cough, and coryza; she never had fever nor oxygen supplementation. Hydroxychloroquine and lopinavir/ritonavir were started, and the antiviral drug was replaced with darunavir/cobicistat after 2 days for diarrhea. Immunosuppressant levels were closely monitored, and we observed very high tacrolimus trough levels despite initial dose reduction. The patient was left with steroid therapy alone. The peculiarity of clinical presentation and the management difficulties represent the flagship of our case report. We stress the need for guidelines in transplant recipients with COVID‐19 infection with particular regard to the management of therapy.